(untitled) (Semiárida, 2025)
Cerro de la Caballada is a formation associated with the bluffs that follow the Negro River in Carmen de Patagones (Buenos Aires). Reaching 45 m at its highest point, it is a national historical monument and a sacred site for the people who preexisted the Argentine State. The formation covers 12 ha of the Monte-Espinal ecoregions and includes some species characteristic of the bluffs, although in recent years, urban growth has modified its connection with other Monte patches. Our objective was to characterize the richness of floral visitors of native plants at Cerro de la Caballada, in order to assess its potential value as a refuge for pollinators. Bimonthly visits were made between spring 2023 and summer 2024, recording the floral visitors observed on native plants. A total of 52 arthropod species belonging to the orders Coleoptera, Diptera, Hemiptera, Hymenoptera, Lepidoptera, Mantodea, and Araneae orders were identified. The order with the greatest species richness was Hymenoptera, followed by Lepidoptera and Coleoptera. Of the total recorded, two exotic species and several members of families with important roles as pollinators, biological controllers, and seed dispersers were identified. These preliminary results represent the first survey of the richness of floral visitors in the Monte of Patagones. By conducting this survey in a peri-urban relict, we expect to gather information for promoting restoration and conservation efforts at the site, as it could represent an important reservoir of biodiversity.